EPEN-02. FUNCTION AND DEPENDENCY OF NF-KB ACTIVITY IN C11ORF95-RELA FUSION EPENDYMOMA. (1st June 2021) - Stuckert, Austin; Arabzade, Amir; Zhao, Yanhua; Chen, Hsiao-Chi; Mack, Stephen
Abstract: Introduction: Ependymoma is an aggressive type of pediatric brain tumor resistant to chemotherapy, with treatment to date limited to surgical resection and radiation. Thus, identification and validation of molecular targets that can translate into clinical trials in ependymoma is desperately needed to improve patient outcomes. Over 70% of supratentorial ependymoma are driven by an oncogenic fusion between C11orf95 and Rela (denoted CR FUS ). CR FUS expression initiates ependymoma development in mice by potentially acting as an oncogenic transcription factor and disrupting gene expression programs. We hypothesized that specific CR FUS interacting proteins are required for tumor formation and could represent lead therapeutic targets. Methods: To study CR FUS ependymoma, a natively-forming tumor model of CR FUS generated by in utero electroporation of the developing mouse brain was utilized. Tumor cells were isolated and then subjected to nuclear Rapid Immunoprecipitation and Mass Spectrometry Analysis of Endogenous Proteins (RIME) of HA-tagged CR FUS protein. Immunoprecipitation and Western Blot (IP-WB) were utilized to probe for leading protein interactions. Results: We identified NF-kB proteins consistent with canonical Rela mediated transcription (NFKB1 and NFKB2) as well as novel protein interactomes that converged on RNA splicing and translational regulation. In addition, we identified a large series of novel chromatin-binding proteins as candidates potentially required for CR FUS mediated tumorigenesis. Conclusions: Further study is ongoing to validate key CR FUS protein interaction dependency on tumor development. ChIP-Seq (chromatin immunoprecipitation with massively parallel DNA sequencing) and CUT&RUN (cleavage under target and release using nuclease) assays have been employed to further analyze the functional role of canonical Rela pathway members. By interrogating these mechanisms, novel therapeutic targets and pathways may be identified in parallel with dissecting the molecular basis of CR FUS driven ependymoma.